(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The synthesis of nanoparticles is an essential element of nanotechnology, because of its potential for use in chemotherapies, the interest in this area of research is expanding. For the synthesis of silver nanoparticles, the chemical reduction technique was used. According to these investigations, the particles have an average size of 16 nm and are mainly spherical in shape. Additionally, A dose-dependent cytotoxicity was also shown by the produced AgNPs against a human colon cancer cell line (HT29). At 72 hours of incubation, it was discovered that the inhibitory concentration (IC50) values for HT29 cells were 48.12 g/ml. The use of AO/EtBr labelling demonstrated an apoptotic induction. The current findings clearly suggested that HT29 cell lines treated with AgNPs would exhibit anticancer activity.